NO2 dataset over Poland and main Polish cities based on OMI observations (2010-2020), TROPOMI observations (2018 - 2021) and CAMS service (2018 - 2021) - Ugboma, Emeka; Stachlewska, Iwona (RepOD, 2022)
The dataset comprises the nitrogen dioxide (NO2) tropospheric column density obtained from the satellite instruments: Ozone Monitoring instrument (OMI) and Tropospheric Monitoring Instrument (TROPOMI), as well as Copernicus Atmosphere Monitoring Services (CAMS) atmospheric data store. The dataset covers two domains: the entire Poland and the main Polish cities.The data set comprises four files:1. OMI_PL_cities.zip – a compressed archive containing 18943 Netcdf-4 format files, each in the form of 2-dim maps of pixels, each file contains the L3 tropospheric column density of nitrogen dioxide (in molec/cm2), obtained for the long-term data form 00:00:00 UTC January 1, 2010 and 00:00:00 UTC December 31, 2020, for the following cities in Poland:Bialystok (domain: 52.97N, 21.70E; 53.53N, 23.64E): 2, 613 files.Gdansk (domain: 54.17N, 17.57E; 54.43N, 18.65E): 2,747 files.Katowice (domain: 50.20N, 18.52E; 50.54N, 19.42E): 2,714 files.Krakow (domain: 49.92N, 19.56E; 50.25N, 20.29E): 2, 670 files.Lodz (domain: 51.40N, 18.88E; 51.99N, 20.14E): 2,794 files.Warsaw (domain: 51.99N, 20.63E; 52.43N, 21.71E): 2,808 files.Wroclaw (domain: 50.90N, 16.26E; 51.49N, 17.69E): 2,597 files.Note: The missing value is -1.267650e+30. Other attributes are listed in the attributes section of the netcdf file.2. TROPOMI_PL_cities_COVID-19.zip - a compressed archive contains a total of 3132 Netcdf-4 files, each in the form of 2-dim maps of pixels, containing the L3 tropospheric vertical column of nitrogen dioxide (in mol/m2), for the following periods:00:00:00 UTC 1 May – 00:00:00 UTC 30 June, 2018 (for this year data available only from May).00:00:00 UTC 1 March – 00:00:00 UTC 30 June, 2019.00:00:00 UTC 1 March – 00:00:00 UTC 30 June, 2020 (corresponding to COVID-19 lockdown over Europe).Coverage for selected Polish cities (lat, long of each city-domain is defined as in OMI):Bialystok: 402 filesGdansk: 354 filesKatowice: 284 filesKrakow: 288 filesLodz: 348 filesWarsaw: 1097 filesWroclaw: 359 filesNote: The fill values are removed. Other attributes are provided in the attributes section of the netcdf file.3. TROPOMI_PL_months.zip - a compressed archive containing 36 Netcdf-4 format files, containing the L3 tropospheric vertical column of nitrogen dioxide (in mol/m2) in the form of a map (domain of Poland: 48.68N, 13.55E; 55.50N, 24.71E) for data acquired from 00:00:00 UTC June 1, 2018 to 23:59:59 UTC May 31, 2021 (36 months). The fill value is -9.969210e+36. Other attributes are provided in the attributes section of the netcdf file.4.  CAMS_PL_months.zip is a compressed archive containing 32 NetCDF-4 format files containing total column nitrogen dioxide (in kg/m2) in the form of a map (domain of Poland: 48.68N, 13.55E; 55.50N, 24.71E) for data obtained from 00:00:00 UTC June 1, 2018 to 23:59:59 UTC May 31, 2021. Note: 31 files correspond to NO2 monthly retrieval for 31 months (June 1, 2018 – Dec 31,2020). 1 file (CAMS_NO2_202101-202105.nc) corresponds to NO2 monthly retrieval for 5 months (January 1 – May 31, 2021) in a single netcdf-4 file format. These 32 files cover the entire Polish domain for 36 months. ATTENTION:We offer free access to this dataset. But the user is encouraged to let the Remote Sensing Laboratory know how the data is being used by sending an email to rslab@fuw.edu.pl.If this dataset is used in scientific communication (e.g. a publication, a presentation/poster at a conference, or a thesis), we would like to ask to add the following statement in the Acknowledgments: "We thank the data originators E. Ugboma and I.S. Stachlewska for the preparation of this quality-assured data sets within activities of the Remote Sensing Laboratory at the Faculty of Physics of the University of Warsaw, Poland."